2012
DOI: 10.1016/j.foodchem.2012.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alkali treatment on structure and function of pea starch granules

Abstract: The effect of alkaline treatment on the structural and functional properties of pea starch granules was studied using a range of characterization methods including amylose content, scanning electron microscopy (SEM), X-ray diffraction (XRD), (13)C nuclear magnetic resonance (NMR), swelling power, differential scanning calorimetry (DSC), the Rapid Visco Analyser (RVA) and in vitro digestibility. The amylose content decreased by about 20-25% after 15days of alkaline treatment and there were small decreases in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
86
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(100 citation statements)
references
References 28 publications
(39 reference statements)
13
86
0
1
Order By: Relevance
“…The X-ray pattern of native and alkali modified HCN starches showed characteristics peaks at about 5.7°, 15°, 17.30°, 18.87°, 23.3°a nd 26.39°. The results are in agreement with the findings of Karim et al [3] and Wang and Copeland [23] who have reported a similar C-type pattern of native and alkali treated sago and pea starch, respectively. However, the intensity of the predominant diffraction peak at 17.30°2h decreased after alkali treatment with 0.5 % NaOH.…”
Section: Ray Diffractionsupporting
confidence: 93%
“…The X-ray pattern of native and alkali modified HCN starches showed characteristics peaks at about 5.7°, 15°, 17.30°, 18.87°, 23.3°a nd 26.39°. The results are in agreement with the findings of Karim et al [3] and Wang and Copeland [23] who have reported a similar C-type pattern of native and alkali treated sago and pea starch, respectively. However, the intensity of the predominant diffraction peak at 17.30°2h decreased after alkali treatment with 0.5 % NaOH.…”
Section: Ray Diffractionsupporting
confidence: 93%
“…The first weight loss, at temperatures close to 100 °C, was small and was due to water evaporation and volatilization of small molecules from the samples. The second weight loss, between 255 and 470 °C, was significant and was due to the degradation of the starch macromolecules themselves (Wang and Les 2012).…”
Section: Tga Analysismentioning
confidence: 98%
“…Regarding the influence of alkaline conditions on starch, many studies have attempted to elucidate the underlying mechanisms (Cardoso, Putaux, Samios & Da Silveira, 2007;Nadiha, Fazilah, Bhat & Karim, 2010;Coperland, 2012 andCai, Yang, Man, Huang, Wang &Zhang, 2014). According to Yamamoto, Makita, Oki and Otani (2006), under strong alkaline conditions it is known that starch gelatinizes even at room temperature.…”
Section: Introductionmentioning
confidence: 99%